1977
DOI: 10.1063/1.324099
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation of silicon in various oxygen partial pressures diluted by nitrogen

Abstract: Oxide growth kinetics of SiO2 films grown on silicon at 950 to 1100 °C in an O2/N2 mixture is empirically studied. It is found that a linear-parabolic law is in excellent agreement with the oxidation data under the oxygen partial pressure PO2 of 1 or 10−1 atm. However, a parabolic law is obtained at 10−2 atm, and an inverse-logarithmic law at 10−3 atm. The Mott-Cabrera oxidation rate equation is adapted to the thermal oxidation of silicon in the case of PO2≲10−2 atm. Finally, 43.9 kcal/mole is derived as the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
3
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 14 publications
7
51
3
3
Order By: Relevance
“…Although measurements at low pressure show quantitative discrepancies among different authors, as far as we know, no one has observed the predicted trend n → 1. In addition to the results of Massoud et al, 8 those of Kamigaki et al, 15 Ganem et al, 18 von der Meulen et al, 14 and Ludstek et al 19 exhibit values of n clearly lower than 1 for oxygen pressures below 0.1 atm in oxidation experiments on Si͑100͒. On the other hand, we have found no experimental curve where the DG limit is reached at low pressure.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Although measurements at low pressure show quantitative discrepancies among different authors, as far as we know, no one has observed the predicted trend n → 1. In addition to the results of Massoud et al, 8 those of Kamigaki et al, 15 Ganem et al, 18 von der Meulen et al, 14 and Ludstek et al 19 exhibit values of n clearly lower than 1 for oxygen pressures below 0.1 atm in oxidation experiments on Si͑100͒. On the other hand, we have found no experimental curve where the DG limit is reached at low pressure.…”
Section: Discussionsupporting
confidence: 51%
“…This leads to the unexpected prediction that the pressure dependence should recover proportionality and the initial oxidation enhancement should disappear for O 2 pressure that is low enough. Fortunately, there are several experiments at subatmospheric pressure [13][14][15] ready to test this prediction. This point will be addressed in Sec.…”
Section: Motivation For the Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Si 2p core-level spectra have been recorded while the chamber pressure was held at 100 mTorr of water vapor pressure or ϳ10 4 times higher than in prior XPS studies of Si oxidation. The samples were cut from commercially available Si͑100͒ wafers, 3 cleaned in a boiling solution of H 2 SO 4 / H 2 O 2 for 10 min, rinsed in deionized water, and dipped in a 50% HF solution for 30 s. A thin oxide layer passivating the surface is then grown by immersing the sample in HCl: H 2 O 2 :H 2 O=1:1:4 at 80°C for 10 min. The oxide layer is removed after transferring the sample inside the chamber by repeated cycles of direct current flow heating the surface up to 1000°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the case of thinner layers, it has been shown that the DG model needs to be modified; several models have been proposed to explain much faster growth rates in the early stages of oxidation. 2,3 A complete understanding of oxidation kinetics in the fast regime still remains a challenging problem to be solved. 4 From an experimental point of view, the difficulty of identifying the growth mechanism in the early stages of oxidation arises from the lack of high-precision tools for monitoring growth rates in situ at pressures that are realistic from a technological point of view.…”
Section: Introductionmentioning
confidence: 99%